Information systems : development, applications, education : 10th SIGSAND/PLAIS EuroSymposium 2017, Gdansk, Poland, September 22, 2017, Proceedings /: development, applications, education : 10th SIGSAND/PLAIS EuroSymposium 2017, Gdansk, Poland, September 22, 2017, Proceedings. ([2017]) - Unknown
No abstract available